2021
DOI: 10.3390/diagnostics11060999
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Value of Circulating Cell-Free DNA for Cholangiocarcinoma

Abstract: The analysis of cfDNA has been applied as a liquid biopsy in several malignancies. However, its value in the diagnosis and prognosis of cholangiocarcinoma (CCA) have not been well defined. We aimed to investigate the diagnostic and prognostic values of cfDNA level and tumor-specific mutation in circulating DNA (ctDNA) in CCA. The plasma cfDNA levels from 62 CCA patients, 33 benign biliary disease (BBD) patients and 30 normal controls were quantified by fluorescent assay. Targeted probe-based sequencing of 60 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Yang et al [ 113 ] showed that CTCs were associated with more-aggressive tumour characteristics and were independently associated with a poorer survival in patients with cholangiocarcinoma. Wintachai et al [ 114 ] investigated the diagnostic and prognostic values of plasma cfDNA levels from 62 cholangiocarcinoma patients, 33 benign biliary disease patients and 30 normal controls. They demonstrated a superior diagnostic efficacy of cfDNA in detecting cholangiocarcinoma than CEA and CA19-9.…”
Section: Liquid Biopsy In Cholangiocarcinomamentioning
confidence: 99%
“…Yang et al [ 113 ] showed that CTCs were associated with more-aggressive tumour characteristics and were independently associated with a poorer survival in patients with cholangiocarcinoma. Wintachai et al [ 114 ] investigated the diagnostic and prognostic values of plasma cfDNA levels from 62 cholangiocarcinoma patients, 33 benign biliary disease patients and 30 normal controls. They demonstrated a superior diagnostic efficacy of cfDNA in detecting cholangiocarcinoma than CEA and CA19-9.…”
Section: Liquid Biopsy In Cholangiocarcinomamentioning
confidence: 99%
“…Additional prognostic biomarkers might enable more accurate patient risk assessment and stratification in clinical trials. Predictive biomarkers for selecting the optimal therapy, such as circulating tumour DNA-based assays for FGFR2 fusions and IDH1 mutations 176,177 , are already in clinical use and will push the field forward. Finally, additional pharmacodynamic biomarkers capable of tracking disease evolution more accurately than the carbohydrate antigen 19-9 (CA 19-9), which is a tumour marker used in the management of biliary and pancreatic cancer, and that can reveal the emergence of drug resistance are warranted 178 , as shown for resistance to FGFR2 inhibitors 179 .…”
Section: Addressing Clinical Needsmentioning
confidence: 99%
“…We do agree, however, on its value as another tool to monitor treatment response and relapse post-surgical resection. Soon, circulating-tumor DNA (ctDNA) may become the tumor marker of choice, as the ctDNA level showed up to 89% sensitivity and 97% specificity to diagnose CCAs, outperforming both CA19-9 and CEA ( 7 ). Further research is on its way to determine the impact of liquid biopsy in this setting.…”
Section: Tumor Markers For Iccamentioning
confidence: 99%